Analysis of the influence of trust, risk perception On online purchase decisions (study on shopee consumers in Durikulon village) - Widar Ningsih; Muhamad Rifa'I; Aryo Bimo Setya Permana (Jurnal Scientia, 2024)
Along with the development of e-commerce in Indonesia, customers are increasingly favored by shopping online to fulfill their needs. This study aims to understand the effect of trust, perceived risk on online purchasing decisions on shopee consumers in Durikulon village. This type of research is quantitative with random sampling technique. Data collection was obtained from 80 respondents with a questionnaire consisting of questions with a Likert scale. The data analysis method used to determine the effect of trust (X1) and risk perception (X2) on purchasing decisions is multiple linear regression and coefficient of determination, while to find out there is whether or not the influence is partially or individually significant, namely the t test and simultaneously together, namely the F test. The results of multiple linear regression obtained are Y = 0.898 + 0.667X1 + 0.316X2, the most dominant variable is Trust (X1) with a beta of 0.898. The results of the calculation of the partial confidence t test (X1) obtained a tcount value of 6,000 > ttable 1,991. So Ho rejected Ha accepted. Risk perception variable (X2) obtained tcount value of 5.189 > ttable 1.91. So Ho rejected Ha accepted. F test results can be obtained Fcount 60,044 > Ftable 3,12 which indicates that Ho is rejected Ha is accepted. Based on the results of the research above, it can be concluded that overall the independent variables have a significant value in a positive direction. The trust variable has the most dominant value compared to the risk perception variable. The trust and risk perception variables also have a significant influence either partially or simultaneously on the dependent variable. namely the purchase decision.